Axial and hysteretic behavior of T-shaped steel–concrete composite shear walls. (April 2022) - Wang, Yunhe; Guo, Lanhui; Li, Hongda; Fu, Feng
Abstract: Multi-partition steel tube formed T-shaped composite shear wall is a new type of composite wall which enhances the structural performance compared to a traditional composite shear wall. To clearly understand the behavior of such shear walls, eight half-scaled specimens were tested to study their axial and seismic behavior. The failure mechanism, structural behavior and energy dissipation ability were observed according to the experiments. The axial experiments showed that the strength of such cross-section was higher than the sum of capacities of concrete and steel tube as the multi-partition steel tube could confine the concrete well. Meanwhile, the ductility of specimens was good. For seismic experiments, the specimens exhibited high strength, good ductility and excellent energy dissipation ability. When the axial load ratio increased, the lateral load resistance capacity and energy dissipation capacity increased obviously. Although the axial load ratio was beyond the limitation of the current Chinese standard, the drift angle could still satisfy the requirement of the standard. The experimental results were used to compare with those calculated results according to some codes including EC4, CECS and AISC.